2005
DOI: 10.7773/cm.v31i11.83
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses and wound healing in the polychaete Eurythoe complanata (Annelida: Amphinomidae) exposed to copper

Abstract: Se dividieron grupos de poliquetos, controles y expuestos a 0.4 mg Cu +2 L -1 (2.14 mg CuSO 4 5H 2 O L -1 ; 30% 96 h-CL 50 ) por siete días, en tres grupos: sensibilizados y no sensibilizados con Micrococcus lysodeikticus para evaluar la actividad de lisozima del fluido celómico, y otro sensibilizado con levaduras inactivadas por calor para evaluar la respuesta fagocítica de los celomocitos. La lisozima fue medida a 2 h y la fagocitosis a los 15 min después de la sensibilización inmunológica. Además, se evaluó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The combined effect (copper + bacterial injection) showed an inhibition of the activity compared to xenobiotic exposition only. Contrary to what has been suggested by (Gagnaire et al, 2007), who reported that some genes involved in defence were up-regulated in Crassostrea gigas following combined exposure to pesticides and bacteria, the slight decrease in activity in the group with combined treatment of CuSO4 and E. coli is due to the immunosuppressive action of the metal, as (Zapata-Vívenes et al, 2005) observed in acute copper exposure; an excessive accumulation of copper in the body can trigger molecular and/or cellular changes, such as oxidative damage (Nusetti et al, 2001), when an infection occurs, resulting in negative effects on LYS function. As previously indicated by (Martinez, 2012) for polluted areas of the Gulf of Cariaco, these alterations can occur in polychaetes subjected to bacterial stress inhabiting copper contaminated environments.…”
Section: Discussioncontrasting
confidence: 97%
“…The combined effect (copper + bacterial injection) showed an inhibition of the activity compared to xenobiotic exposition only. Contrary to what has been suggested by (Gagnaire et al, 2007), who reported that some genes involved in defence were up-regulated in Crassostrea gigas following combined exposure to pesticides and bacteria, the slight decrease in activity in the group with combined treatment of CuSO4 and E. coli is due to the immunosuppressive action of the metal, as (Zapata-Vívenes et al, 2005) observed in acute copper exposure; an excessive accumulation of copper in the body can trigger molecular and/or cellular changes, such as oxidative damage (Nusetti et al, 2001), when an infection occurs, resulting in negative effects on LYS function. As previously indicated by (Martinez, 2012) for polluted areas of the Gulf of Cariaco, these alterations can occur in polychaetes subjected to bacterial stress inhabiting copper contaminated environments.…”
Section: Discussioncontrasting
confidence: 97%
“…4, 5). The 2003The , 2005, and 2010 CP El Niño events had a strong impact on the biology of TCSLu; their impact was similar to the impact of the Blob in 2014 and the impact of the 2015-2016 EP El Niño (Fig. 4).…”
Section: Discussionmentioning
confidence: 83%
“…Contrary to the findings by Arroyo-Loranca et al (2015) for the transect off Punta Eugenia, the El Niño events from the twenty-first century did have strong effects on the biology of TCSLa and TCSLu. The -2005The and 2009 El Niño events were of the CP type; in our study, only the 2015-2016 El Niño event was of the EP type (NOAA 2017b). The CP type events tended to occur more often in the twenty-first century (Lee and McPhaden 2010).…”
Section: Discussionmentioning
confidence: 86%
“…In the family Sabellidae, the mucosal matrix is also involved in lubrification, gaseous exchange [10], and in cementing different substances in tube building, mixing feces, pseudofeces and sediment [12]. Many polychaetes are slow moving or sessile, thus they have developed a number of secreted compounds of the immune system [13,14]; among these immunomodulators, lysozyme-like activity was found in various polychaete species [15,16,17]. All these studies, however, concern the coelom, while Stabili et al [9] examined the presence of lysozime-like activity in the mucus, which serves as a medium to exude antibacterial substances.…”
Section: Introductionmentioning
confidence: 99%